EKSISTENSI HUKUM PENGUPAHAN YANG LAYAK BERDASARKAN KEADILAN SUBSTANTIF - Zulkarnain Ibrahim (Jurnal Dinamika Hukum, 2013)
Appropriate wage Law must base on labour regulation and labour acts, fulfil substantive justice criteria related with continuous work relationship, peaceful and harmony with business owner, and also had rights and proper wage. The idea to formulate regulation in wage sector transparently by wage method, survey mechanism, structured, and scaled as well as surveillance/supervision. Besides that, encourage Labour Organization/Worker Association to implement their obligation to protect and to defence the rights and interest of their members. Result of wage law reformulation hopefully could foster Indonesia’s labour legal system which had equal values universally. Keywords: System, undertaking, worker, substantive justice.